Strategic Plan 2019-2024 (Caribbean Court of Justice Port-of-SpainTT, 2019)
The Strategic Plan represents the united voice of the employees and stakeholders of the CCJ who continue to enable improvement and a highter standard of court performance. The theme for the new Plan reflects the Court's planned strategic and operational responses to the issues and expectations of its stakeholders. The CCJ's mandate has been revisited and is reflected in the new Mission and Vision Statements that speak to the unwavering focus on the development of a Caribbean jurisprudence.